Impacto de las remesas en el crecimiento económico: Un análisis econométrico para la región de América Latina y el Caribe, periodo 1986-2020 - Muñoz Ambuludí, Stefania Michelle (2023)
Growth prospects for Latin America and the Caribbean (LAC) have remained unstable, leading to a 6,7% GDP slowdown in 2020, while remittances rebounded 8% in the same period. Thus, the general objective pursued by this study is to analyze the impact of remittances on economic growth in the Latin American and Caribbean Region during the period 1986-2020, through the use of econometric techniques, in order to establish policies that improve the economic performance of the region. The data used was obtained from the World Bank (2020) for 14 LAC countries. The theory is based on Solow's (1956) model, which alleges that production increases by improving capital endowments, and Stark's (1991) NELM approach, which establishes that remittances modify the production function by softening financial restrictions. The methodological strategy uses a Generalized Least Squares (GLS) model, in addition the Westerlund (2007) cointegration test was used and the long-term coefficients were estimated using an AMG model, finally, the Dumitrescu and Hurlin (2012) causality test was used. In general, the results indicate that remittances do not contribute to generating economic growth, maintaining a negative and significant relationship with GDP per capita. On the other hand, the existence of a long-term equilibrium relationship between remittances and economic growth is confirmed, while the causal relationship between these variables turns out to be null. The political strategy focuses on the promotion of employment, financial education programs and access to financing so that remittances influence the development of productive activities.